Optimizing preplant irrigation for maize under limited water in the High Plains - Schlegel, A. (2020)
The purpose of the study was to determine preplant irrigation amount and irrigation capacity combinations that optimize yield, water productivity, and precipitation use efficiency (PUE) and minimize soil water evaporation losses prior to planting. The CERES-Maize model embedded in the RZWQM2 model in combination with long-term climatic data from 1986 to 2014 for southwest Kansas were used for this research. Experimental data from 2006 to 2009 was used to calibrate and validate the model. Increasing preplant irrigation resulted in significantly higher soil water evaporation losses prior to planting at all irrigation capacities. Overall preplant irrigation is beneficial under very limited irrigation capacity but is not necessary under sufficient irrigation capacity in most years. The decision to apply preplant irrigation should be evaluated and implemented carefully in combination with other agricultural water management technologies and strategies such as soil water monitoring, drip irrigation, and residue management.